PENINGKATAN GIZI IBU HAMIL DENGAN FORMULA MULTI GIZI DALAM UPAYA UNTUK MENINGKATKAN PERTUMBUHAN, PERKEMBANGAN MENTAL DAN MOTORIK BAYI - Haslinda, Haslinda (Universitas Negeri Medan, 2013)
ABSTRACTThis study aims to assess the effect of multi-nutrient supplement efforts to provide pregnant women with fetal growth and birth growth also for the mental and motor development of infants. The research was conducted over three stages; the first year of this study has been tested to the mice. The research was carried out on pregnant women in the District Tobasa. Sample of 60 people and were treated for 9 months to pregnant women to bear children. Design research to be conducted is a prospective epidemiologic design (cohort studies) in the form of the intervention and comparison (control) were given control of the sample selected randomly, so called